2015
DOI: 10.1371/journal.pone.0131378
|View full text |Cite
|
Sign up to set email alerts
|

Individuals Who Believe in the Paranormal Expose Themselves to Biased Information and Develop More Causal Illusions than Nonbelievers in the Laboratory

Abstract: In the reasoning literature, paranormal beliefs have been proposed to be linked to two related phenomena: a biased perception of causality and a biased information-sampling strategy (believers tend to test fewer hypotheses and prefer confirmatory information). In parallel, recent contingency learning studies showed that, when two unrelated events coincide frequently, individuals interpret this ambiguous pattern as evidence of a causal relationship. Moreover, the latter studies indicate that sampling more cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
59
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(69 citation statements)
references
References 51 publications
6
59
3
1
Order By: Relevance
“…The current findings complement recent research by Blanco et al (2015). As noted in the Introduction, they found that when superstitious people were asked to test a causal relationship (the effect of a new medicine), they more frequently intervened in the system (gave the patient the medicine) than did less superstitious people.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The current findings complement recent research by Blanco et al (2015). As noted in the Introduction, they found that when superstitious people were asked to test a causal relationship (the effect of a new medicine), they more frequently intervened in the system (gave the patient the medicine) than did less superstitious people.…”
Section: Discussionsupporting
confidence: 88%
“…Participants reporting high levels of superstitious beliefs tended to rate the button press as having caused the light to illuminatea causal illusionwhereas those with low superstition were less susceptible to this illusion and tended to (correctly) see the events as unrelated. The present data make an important additional contribution to the superstition literature by examining the operation of basic causal learning mechanisms that are often assumed to be related to superstitions (see Blanco et al, 2015;Yarritu, Matute, & Luque, 2015). The relationship held both for the magnitude of people's causal judgements (i.e., the degree of causality people saw the button press as possessing) and also the propensity to infer causation (i.e., whether people saw a causal relationship between the two events, irrespective of its magnitude).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…For instance, Brugger and Graves (Brugger & Graves, 1997) showed that participants who scored high on a magical ideation scale tested fewer hypotheses -but retrospectively believed in many more hypotheses -than participants who scored low on that scale. Similarly it has been found that paranormal believers more readily develop illusions of control on a simple contingency learning task in the laboratory (Blanco, Barberia, & Matute, 2015;Matute, Yarritu, & Vadillo, 2011). These studies indicate a close relation between magical thinking and the feeling of control and that people prone to magical thinking tend to perceive more illusory contingencies than skeptics.…”
Section: Introductionmentioning
confidence: 58%
“…Similarly, paranormal beliefs presume a fundamental relation between two objectively unrelated events, e.g., as in the case of mental healing or thoughttransfer. It has been argued that a key feature of magical thinking is indeed the perception of illusory relations in patterns of random noise (Malinowski & Redfield, 1948) and many studies have shown that participants who engage in magical thinking, are also prone to the perception of illusory contingencies and illusory patterns (Blackmore & Moore, 1994;Blanco et al, 2015;Krummenacher, Mohr, Haker, & Brugger, 2010;Riekki et al, 2013;van Elk, 2013). Following the compensatory control framework, it is to be expected that the perception of illusory patterns and contingencies provides a sense of order, meaning and control -especially in case when personal feelings of control are low.…”
Section: Discussionmentioning
confidence: 99%